Analisis Yuridis terhadap Tenaga Kerja Asing “Tiongkok” yang Dipekerjakan di Kota Batam Ditinjau dari Hukum Ketenagakerjaan - Agustianto Agustianto; Rodeen Chenggaliex Chenggaliex (Fakultas Hukum, Universitas Internasional Batam, 2017)
This writing discusses the problems of foreign workers employed by employers in terms of labor law. The purpose of this study is to find out the problems that occur to the foreign workers